Report on the Observance of Standards and Codes, Accounting and Auditing : Module B - Institutional Framework for Corporate Financial Reporting, B.1 Commercial Enterprises (including SMEs) - World Bank (World Bank, Washington, DC, 2017)
The purpose of this report is to gain an understanding of the general financial reporting and audit requirements for commercial enterprises in a jurisdiction as established by law or other regulation (for example, companies’ act). Commercial enterprises are defined as companies established with a profit-making objective that do not issue equity and debt on a public exchange, are not financial institutions (such as banks or insurance companies), and are not owned and controlled by the state. The definition of commercial enterprises also includes small and medium sized enterprises (SMEs). The focus of this report is commercial enterprises with limitations of liability, such as limited liability companies (LLCs) and joint stock companies. The report is structured as follows: statutory framework; financial reporting requirements for commercial enterprises; statutory audit and other forms of independent assurance; audit committees; filing and publication of financial statements; monitoring and enforcement: financial reporting; and corporate governance.